Quantitative and qualitative benefits of translanguaging pedagogic practice among first graders in multilingual classrooms of Lundazi district in Zambia - Nyimbili, Friday; Mwanza, David Sani (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The aim of the paper is assess the pedagogical benefits of translanguaging using a quasi-experiment where two literacy classes with similar sociolinguistic composition were taught differently. In this case, the control class strictly followed the ‘monolingual’ language policy while the experimental class was taught using translanguaging. The idea was to see whether translanguaging could lead to any measurable literacy development benefits on the learner. Through interviews with the class teacher and classroom observations, the paper also sought to bring out the qualitative benefits which were observed or experienced throughout the experiment. A total of 82 pupils participated in the study with one teacher who taught both classes. Quantitative data was analysed using SPSS and a Levene’s test of variance was used to analyse the test results while thematic analysis was used for qualitative data analysis. Post experimental test results showed higher average mean scores for the experimental group (M=15.10) than the control group (M=11.71). The Cohen’s d=0.98 for the post-test showed the large effect size above .8. The performance of learners in the experimental group was significantly different from the control group [t (52.960 = 4.454, p<0.001]. Thus, the difference in literacy performance can be attributed to the translanguaging practices which were used to teach literacy in the experimental class. Additional results showed that as a result of translanguaging, there was increased learner classroom participation, multiliteracy development, cultural preservation and learners’ identity affirmation. The study concludes that when the curriculum is decolonised and the classroom is liberated through recognition of learners’ linguistic repertoires, learning outcomes improve. The paper makes a unique contribution to knowledge by providing objective data from an experiment to show the educational benefits of translanguaging.